Recurrent EWSR1:COLCA2 Fusions Define a Novel Sarcoma With Spindle/Round Cell Morphology and Strong Predilection for the Sinonasal Tract. (14th March 2023) - Agaimy, Abbas; Baněčková, Martina; De Almeida, John; Dickson, Brendan C.; Dimmler, Arno; Hartmann, Wolfgang; Laé, Marick; Pablik, Jessica; Schubart, Christoph; Skálová, Alena; Stoehr, Robert; Trautmann, Marcel; et al.
Abstract : The last 2 decades have attended a dynamic evolution in the nosology of poorly differentiated sinonasal tract malignancies, with several new molecularly defined entities having been described in addition to delineation of the genetic driver/s of some established older entities. These discoveries, however, mostly concerned epithelial-derived neoplasms (carcinomas). Adamantinoma-like Ewing sarcoma and biphenotypic sinonasal sarcoma are the major representatives of the newly defined mesenchymal categories. The colorectal cancer associated 2 (COLCA2) has been discovered recently as a colorectal cancer risk gene locus, but fusions involving this gene have not been well characterized. We, herein, describe clinicopathologic and molecular features of a novel sinonasal sarcoma characterized by undifferentiated spindle/round cell morphology and defined by recurrent EWSR1::COLCA2 fusions. All patients (n=5) were adults (3 female and 2 male) with a median age of 46 years (range, 23 to 60 y). The tumors originated in different subsites of the sinonasal tract with frequent multisite involvement. Original diagnoses were undifferentiated or unclassified round cell/spindle cell neoplasm/sarcoma (n=4) and neuroendocrine carcinoma (n=1). Surgery with or without adjuvant chemoradiation was the treatment in all cases. At the last follow-up, 1 patient developed multiple local recurrences over 21 years and another developed local recurrence and distant metastasis to bone 27 months after diagnosis. A third patient developed local recurrence 11 months later. Two patients were disease-free at 23, and 24 months. Histology showed nondescript highly cellular neoplasms with an admixture of spindled and round cells disposed into solid sheets and fascicles with brisk mitotic activity. Immunohistochemistry was negative for all lineage-specific markers with only limited focal membranous CD99 (4 of 5 cases) and weak pankeratin (1 of 5 cases) expression. Targeted RNA sequencing revealed an EWSR1::COLCA2 fusion, verified by EWSR1 fluorescence in situ hybridization, in all cases. This series identifies a novel member in the undifferentiated spindle/round cell sarcoma category with strong predilection for the sinonasal tract. None of >10, 000 epithelial and mesenchymal neoplasms tested at the authors' centers during the same period showed this fusion, highlighting rarity of tumors carrying this gene fusion. Accordingly, molecular testing of unclassified sinonasal malignancies/sarcomas showing round and spindle cell morphology is recommended to enhance the identification and further characterization of this entity.